Efficient mitigation of cadmium and lead toxicity in coriander plant utilizing magnetite (Fe3O4) nanofertilizer as growth regulator and antimicrobial agent. Issue 16 (16th December 2022) - Fahad,; Balouch, Aamna; Agheem, Muhammad Hassan; Memon, Sohail Ahmed; Baloch, Abdul Rehman; Tunio, Aqsa; Abdullah,; Pato, Abdul Hameed; Jagirani, Muhammad Saqaf; Panah, Pirah; Gabole, Asif Ali; Qasim, Sana
ABSTRACT: In the present study, Chemical Co-precipitation method was used to synthesize magnetic Iron oxide nanoparticles and applied them as fertilizer. Various sophisticated techniques were employed to confirm the surface morphology and crystalline structure of engineered nanomaterial i.e. TEM, FESEM, FTIR, XRD and BET. The growth and mitigation effects were evaluated in the Coriander plant (root, shoot and leaves) using Fe3 O4 NPs, NPK and without fertilizer in artificially contaminated soil with cadmium and lead solutions (20 mg/L) through ICP-OES. The mitigation percentage in coriander was found to be 97.37, 81.12, 77.79 (Cd) 98.45, 80.77, 75.89 (Pb) using 10 mg/L Fe3 O4 NPs, 100 mg/L NPK and without fertilizer respectively. On the other hand, growth effects were observed in length, 53.3, 33.02, 25.4 cm (Cd) 48.26, 43.18, 38.1 cm (Pb) using similar doses of Fe3 O4 NPs, NPK and without fertilizer respectively.Moreover, excellent antibacterial activity was being disclosed by efficient Fe3 O4 NPsagainst Gram positive and negative bacterium.